Análise da fragilidade ambiental da bacia hidrográfica do Ribeirão dos Cavalos no Munícipio de Itapetininga-SP - Souza, Mônica de (Universidade Federal de São Carlos, 2023)
Environmental research is essential to understanding the landscape and promoting an integrated analysis of the environment. Although numerous techniques and approaches have been refined, the understanding of the landscape as a dynamic system continues to inspire research. The uncontrolled increase in the world population has impacts that harm the ecosystem balance, especially regarding water quality in watersheds. The lack of studies that relate land use and water resources with active urban regions hinders the implementation of effective management measures. With the aim of assisting in territorial planning and watershed management, this study sought to develop spatial data that demonstrate environmental fragility and land use conflicts. The study was developed in the Ribeirão dos Cavalos watershed, located in the municipality of Itapetininga, through geoprocessing techniques where geomorphological and land use and occupation data were evaluated, identifying conflicts arising from their use, as well as environmental fragility and water quality alteration. Through this analysis, it was possible to develop a synthesis vision of the watershed, aiming for conservation and recovery, as well as providing primary data for a possible identification of priority areas in territorial planning, since this area does not have studies related to its fragility.
Analysis of the environmental fragility of the Ribeirão dos Cavalos watershed in the city of Itapetininga-SP
Keywords: Planejamento Territorial; Uso da Terra; Bacia Hidrográfica; Geoprocessamento; Territorial Planning; Land Use; Watershed; Geoprocessing; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOFISICA::SENSORIAMENTO REMOTO; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOGRAFIA FISICA::GEOMORFOLOGIA